The role of producer organizations in promoting farm-level implementation of milk hygiene strategies among dairy farmers in Kenya - Owiti, Magdaline Adhiambo; Mshenga, Patience Mlongo; Sibiko, Kenneth Waluse (University of Life Sciences in Poznań, 2024)
Food safety remains a critical concern globally, particularly in the dairy industry of developing countries, where quality standards are often insufficient. This is attributed to low milk production, poor milk handling practices and domination of the sub-sector by informal and unregulated milk marketing channels. An improvement in the quality of the milk produced is necessary to alleviate concerns about food safety and health. This study employed a multi-stage sampling technique to select a sample of 282 dairy farmers in Meru County, Kenya. Relevant data was collected on identified variables using a structured questionnaire, and a Poisson Regression Model was used to determine the role of producer organizations in promoting farm-level implementation of milk hygiene strategies. The results indicate that producer organization membership has a positive and significant influence on the extent of farm-level implementation of milk hygiene strategies. The findings of this study provide relevant information for policy formulation aimed at improving the performance of producer organizations and the growth of the dairy industry. Therefore, dairy farmers experiencing technical difficulties should be identified and incentivized to actively participate in producer organizations, so as to increase their access to relevant extension services such as training in milk hygiene strategies, which would enhance their implementation of milk hygiene strategies at the farm-level.